Medical Nutrition Therapy: An Essential Component of COPD Care - Daga, Mradul K.; Singh, Shashank; Mawari, Govind (Current Respiratory Medicine Reviews, 2018)
COPD affects all organ systems by inducing chronic systemic inflammation as well as metabolic alterations. Various pharmacological, medical & surgical approaches are available for management of COPD. We can’t ignore the importance of nutrition to promote the sound state of health in all COPD patients. Intake of essential micronutrients in adequate amount as per recommended dietary allowance (RDA) & maintenance of normal body-mass index (BMI) is the fundamental requirement for achieving beneficial effects. Here, in this review, we will discuss all the facts related to the scientific role nutrition plays in the pathogenesis of COPD as well as clinical implications referring to the supplemental benefits of nutrients.
Keywords: Pulmonary cachexia